An Investigation on the Effect of the Ore Particle Size on the Efficiency of Sarcheshmeh Copper Mine Crushing Unit - Mohsen Amir-Rahmat (Canadian Institute of Mining, Metallurgy and Petroleum, 2003)
The ore of Sarcheshmeh copper deposit that has been located in the south ?east of Iran, contains four type of rock that they have their specific hardness and strength according to their alteration type and mineralization. Blasting of these various types of mine rocks prepares various types of size for the product of mine as the feed of concentration. Along the crushing of this feed a few factors effect on the efficiency of the crushing unit. The aim of this project has been the consideration of the effect of ore size on the efficiency of crushing unit. For this investigation along the year 2000 A.D., six sample from feed and six sample from product of crushing unit have been prepared. The results of the screen analyze of these samples has shown that the size of feed has been lesser than the primary plan and the size rate of the product has been bigger than the primary plan. Also in this research the effect of feed size on the quality of product size has been considered.